ANALISIS KAPASITAS SALURAN DRAINASE DI SUB PEMATUSAN KALI RUNGKUT SURABAYA - Asid, Nurul Jannah; Harjanto, Didik; Fanisah, Nurul (NAROTAMA JURNAL TEKNIK SIPIL, 2024)
Surabaya City is the provincial capital as well as the largest city in East Java. Infrastructure development to support the development of the city of Surabaya and the impact that occurs to meet the needs of the community causes the transfer of land functions. As a result, it can increase the impermeable layer on the soil surface which will reduce rainwater seeping into the soil and creating a burden on drainage channels. This should be reviewed against the dimensions of existing drainage channels to minimize flooding. Based on the results of hydrological calculations and hydraulics calculations, conclusions were obtained for the study of the capacity analysis of the drainage channel of the Surabaya Rungkut River Sub-Commissioning as follows: In the 1.25-year anniversary period, the Medokan Rungkut channel has been unable to accommodate flood discharge. In the 5-year anniversary period, the Rungkut Asri channel is no longer able to accommodate flood discharge. And in the 10-year anniversary period, the Rungkut channel was no longer able to accommodate flood discharge. The dimensions of the 3 channels are enlarged so that they can accommodate the flood discharge that occurs. The capacity of the Rungkut channel becomes 6.3 m3/s, the Rungkut Asri channel becomes 5.6 m3/s, the Rungkut Medokan channel becomes 5.6 m3/s. The pump capacity is taken from the Rungkut channel with flood discharge Q10 = 6.1285 m3/s, with a pipe diameter design of 2.25 m and a large water power of 343.6 HP.